The temperature and solvent effect on the structural, thermodynamic and electronic properties of Auxin: A computational study - Alauddin, Md; Barna, Nasima Tabassum; Parvez, Md Masud; Islam, Gazi Jahirul; Matin, Mohammad Abdul (Journal of Bangladesh Academy of Sciences, 2024)
Indol-3-acetic acid (IAA) is the major and naturally synthesized auxin that can regulate plant growth and many physiological processes involving the response to directional light. Computational analysis of the impacts of solvents on different polarity and temperature (100K–1000K) on the structural, thermodynamic, and electrical properties of IAA is done using the density functional theory (DFT) approach. The optimized structure of the IAA molecule shows four (4) stable conformers depending on their energies. The increasing intensities of molecular vibration were seen to generate a rise in enthalpy (H), entropy (S), and specific heat capacity (Cv) with temperature. Conversely, it was found that Gibbs's free energy (G) decreased when temperature increased. Our computations demonstrate that when solvation lowers excitation energies, the UV-light absorption maxima (λmax) are red-shifted in the presence of polar protic, aprotic, and non-polar solvents. Conversely, exothermic and spontaneous behavior is seen in the interactions between IAA and solvents with varying polarity. J. Bangladesh Acad. Sci. 48(2); 193-206: December 2024